Innovation and Adaptation of Social Studies Learning in Curriculum Development - Syafruddin, Syafruddin; Ramadani, Sari; Elnafisah, Dea; Sari, Novita; Rifan, Muhamad (JUPE : Jurnal Pendidikan Mandala, 2024)
Social Sciences is a subject that studies aspects of the field of science related to humans, the environment and the interaction activities between them. There are several complaints about social studies education, such as getting bored easily, not being able to memorize, the lesson material is not related to daily life, and the learning process is monotonous, namely students spend more time listening and taking notes. Apart from that, the implementation of social studies learning tends to deliver material according to textbooks and the methods used are not varied, namely more lecture methods and not using various learning media. So the students' attitudes during the learning process are like joking around with their classmates, sleeping and doing other activities as a result of which the material presented is not understood. So it is very important to determine innovation and adaptation of social studies learning in the development of the current educational curriculum. The method used is library research or literature review. Library research includes general processes such as systematic identification of theories, literature exploration, and analysis of documents that contain information related to the research topic. Based on the results of the study, the forms of social studies learning innovation in curriculum development are; actualization of social studies learning, project-based learning, student-centered approach, use of technology, field trips, connection with the real world, performance-based evaluation, creativity and expression, collaboration between subjects, continuous process improvement. Meanwhile, the form of adaptation itself is by implementing differentiation learning which consists of; content differentiation, process and product differentiation.